Más allá de la criminalización terciaria : análisis y perspectivas para el pos-penado en Colombia (2017)
"In order to raise awareness and generate a reflection on the reality of the post-prisoners in the national territory, this research work aims, first, to reflect the current situation of people who have served a prison sentence, in particular, their possibilities of access to education and work for, later, identify faults in the criminal policy regarding post-punishment re-socialization and propose a new approach in the model of such public policy. In order to fulfill this objective, a quantitative research is proposed, with a descriptive design that uses documentary analysis as a technique for collecting information. The theoretical framework will be composed of several relevant sources to determine the legislation, jurisprudence and doctrine that make public policy, and the reports and statistics proposed, reflect the success, or lack of, both in design and implementation." -- Tomado del Formato de Documento de Grado.